The Diet Problem on Minimizing Vitamin A: Linear Programming Problem - Muhammad Naim Ruslan; Nurul Farihan Mohamed (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology